ANALISIS PERUBAHAN BILANGAN KURVA ALIRAN PERMUKAAN PADA BEBERAPA SKENARIO PEMANFAATAN LAHAN DI SUB DAS LATOMA, DAS KONAWEHA, SULAWESI TENGGARA - Miranda R. Malamassam; Sandra E. Pakasi (Forestry Faculty of Universitas Hasanuddin, 2007)
Sub watershed of Latoma has to be considered as an area of the important regions in South East Sulawesi, because it takes a great responsibility as a water supplier in Konaweha watershed. Konaweha watershed is a source of irrigation and domestic water for Kolaka Regency, Konawe Regency, South Konawe Regency and Kendari Municipality which has been recently in a critical condition. For this reason, it should be well managed. This study was implemented with the aim of establishing model of land use in Latoma sub watershed that can preserve the land and water resources. The method employs a system analysis with simulation technique by using the Run-off Curve Number (CN) model based on Geographical Information Systems (GIS). The result of the research revealed that the run-off curve number is 70,34. It showed that maximum potential water retention or infiltration rate is 107,10 mm. Restructuring of land use pattern should be done to improve the condition of the area to achieve a sustainability objectives. Keywords : Watershed, land use, run-off curve number (CN), GIS